ENDOSCOPY-ASSISTED VITRECTOMY AND MEMBRANE DISSECTION OF ANTERIOR PROLIFERATIVE VITREORETINOPATHY FOR CHRONIC HYPOTONY AFTER PREVIOUS RETINAL DETACHMENT REPAIR. Issue 6 (June 2016) - Lee, Gregory D.; Goldberg, Roger A.; Heier, Jeffrey S.
Abstract : Purpose: To review 6-month outcomes for patients with hypotony secondary to anterior proliferative vitreoretinopathy after previous retinal detachment repair who were treated with endoscopic vitrectomy and anterior membrane dissection. Methods: Retrospective review. All individuals underwent endoscopic vitrectomy with removal of anterior proliferative vitreoretinopathy involving the ciliary body. Outcome measurements included intraocular pressure (IOP), visual acuity, and development of phthisis bulbi. Results: Fifteen eyes of 15 patients had an average of 4.5 previous intraocular surgeries (range 1–8). Forty Percent of eyes had silicone oil at the time of endoscopic surgery. Six months postoperatively, 4 eyes had IOP >11 mmHg while 11 had IOP <6 mmHg. The nonresponder group was older in age, had more previous intraocular surgeries, and a lower preoperative IOP. There were no differences in visual acuity or the development of prephthisis at any point. No eyes underwent enucleation or evisceration. Conclusion: Endoscopy-assisted vitrectomy with removal of anterior proliferative vitreoretinopathy from the ciliary body is an effective treatment for chronic hypotony after previous retinal detachment repair in a minority of cases. The IOP improved in patients who tended to be younger and who had fewer previous intraocular surgeries. Further study is indicated to evaluate long-term outcomes and predictors of surgical success. Abstract : A report on 6-month outcomes for patients with hypotony secondary to anterior proliferative vitreoretinopathy after previous retinal detachment repair who were treated with endoscopic vitrectomy and anterior membrane dissection. Improvement in intraocular pressure was found in a minority of cases: eyes of younger patients who had fewer previous intraocular surgeries.